2002
DOI: 10.1046/j.1464-410x.2002.03055.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of radiation therapy for patients with prostate specific antigen recurrence after radical prostatectomy

Abstract: Objectives To assess the efficacy of salvage/adjuvant radiation therapy (RT) for patients with prostate-specific antigen (PSA) recurrence after radical prostatectomy (RP). Between 1997 and 2001, 52 patients were treated in our institution with RT for PSA recurrence after RP. The mean (range) delay between RP and RT was 30.5 (0.16-105.6) months. Eighteen patients received no hormonal therapy before RT. The failure of RT was defined as three consecutive increases in PSA levels with intervals of ≥ 6 weeks. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Gleason score and high grade prostate cancer was associated with poor biochemical outcome in previous reported studies [ 19 - 30 ]. However, we did not find any significant bDFS difference for patients with a low (≤6) or high (≥7) Gleason scores.…”
Section: Discussionmentioning
confidence: 83%
“…Gleason score and high grade prostate cancer was associated with poor biochemical outcome in previous reported studies [ 19 - 30 ]. However, we did not find any significant bDFS difference for patients with a low (≤6) or high (≥7) Gleason scores.…”
Section: Discussionmentioning
confidence: 83%
“…[14] Conversely, Taille et al evaluated ART failure in patients with BCR after RP and showed that GS ( P = .0395) was an independent predictive factor. [31]…”
Section: Discussionmentioning
confidence: 99%
“…[1012] Whether adjuvant therapy is necessary when RP GS is high (8–10) remains controversial. [1315] Several studies analyzed predictors of biochemical recurrence (BCR) after adjuvant therapy to identify patients who might benefit from radiotherapy; nonetheless, the predictive impact of high RP GS was not consistent.…”
Section: Introductionmentioning
confidence: 99%
“…124 Intermittent ADT is currently only recommended for men 470 years of age with GS r7. 125 Thus, there are a number of uncertainties about the use of ADT in the setting of BR, and there is no consensus on who should receive therapy. Medical practitioners should take into consideration their suspicion that the rising PSA is related to metastatic disease, patient comorbidities, the quality of life of the patient with a known rising PSA (ie, "PSA anxiety"), and the quality of life of the patient while on ADT when making recommendations for the therapy.…”
Section: Adt Post-rp or Post-rtmentioning
confidence: 99%